Feminist Agendas and Democracy in Latin America - Jaquette, Jane S., 1942- (Book collections on Project MUSE., 2009)
This collection links feminist activism and democratization in Latin America, with essays by politically active Latin American women about their experiences addressing women's issues within the context of developing democratic systems in Brazil, Argentina